Undesirable role of remnant PbI2 layer on low temperature processed planar perovskite solar cells. Issue 103 (24th October 2016) - Du, Yangyang; Cai, Hongkun; Wen, Hongbin; Wu, Yuxiang; Li, Zhenglong; Xu, Jian; Huang, Like; Ni, Jian; Li, Juan; Zhang, Jianjun
Abstract : In this work, we carefully study the influence of the remnant PbI2 on the performance of planar PSCs including efficiency and thermal stability by varying the PbI2 stoichiometry of the resultant CH3 NH3 PbI3 . Abstract : Two-step deposition methods for preparing CH3 NH3 PbI3 films are becoming increasingly competitive when considering fabricating perovskite solar cells (PSCs) under ambient conditions, along with possessing the ability to better control their morphology. The surplus PbI2 phase can be detected within the formed CH3 NH3 PbI3 films due to partial conversion of PbI2 to CH3 NH3 PbI3, which causes variation in the PbI2 stoichiometry of the resultant films. In this work, we carefully study the influence of the remnant PbI2 on the performance of planar PSCs including efficiency and thermal stability by varying the PbI2 stoichiometry of the resultant CH3 NH3 PbI3 . Through a further comparative study, the undesirable role of the remnant PbI2 layer on planar PSC performance is exposed, indicating that the remnant PbI2 layer not only greatly impedes carrier extraction and transport, but also accelerates the degradation of the CH3 NH3 PbI3 film. To further eliminate the interference of this phenomenon, low temperature processed planar PSCs approaching 13% efficiency are attained in ambient atmosphere by the modified two-step method with enhanced thermal stability, which has significant potential for future mass production of PSCs and provides insight into the correlation between device performance and the PbI2 stoichiometry of CH3 NH3 PbI3 films.